ChemInform Abstract: On Tetrafluorobromates(III): Crystal Structures of the Dibromate CsBr2F7 and the Monobromate CsBrF4. Issue 8 (25th February 2014) - Ivlev, Sergey; Woidy, Patrick; Sobolev, Vasily; Gerin, Ivan; Ostvald, Roman; Kraus, Florian
Abstract CsBrF4 (I) and CsBr2F7 (II) are prepared by the reaction of stoichiometric amounts of CsF and BrF3 (previously published method).